Immobilization of Rhizomucor miehei lipase onto montmorillonite K-10 and polyvinyl alcohol gel - Babavatan, Ece Ozdemir; Yildirim, Deniz; Peksel, Aysegul; Binay, Baris (TAYLOR & FRANCIS LTD, 2020)
Immobilization of enzymes from different sources on various supports in designed systems increases enzymes' stability by protecting the active site of it from undesired effect of reaction environment. Also, immobilization decreases the cost of separation and facilities the reuse of the enzymes. Therefore, the design of new immobilization enzyme preparations has been an inevitable area of modern biotechnology. Herein, Rhizomucor miehei lipase (RML) was immobilized on montmorillonite K-10 (MMT-RML) by adsorption and in polyvinyl alcohol (PVA-RML) by entrapment to obtain a more stable and active lipase preparation. The free and immobilized lipase preparations were characterized for p-nitrophenyl palmitate hydrolysis. The apparent Michaelis-Menten (K-mapp) constant was almost the same for the free RML and PVA-RML, whereas the corresponding value was 17.7-fold lower for MMT-RML. PVA-RML and MMT-RML have shown a 1.1 and 23.8 folds higher catalytic efficiency, respectively, than that of the free RML. The half-lives of PVA-RML and MMT-RML were found to be 7.4 and 3.4 times longer than the free RML at 35 degrees C, respectively. PVA-RML and MMT-RML maintained 65% and 87% of their initial activities after four reuses. These results showed that the catalytic performance of RML has improved significantly by immobilization.
Keywords: Lipase; immobilization; montmorillonite K-10; polyvinyl alcohol; ENZYME IMMOBILIZATION; COVALENT IMMOBILIZATION; INDUSTRIAL APPLICATIONS; OPERATIONAL STABILITY; BIODIESEL PRODUCTION; ADSORPTION; PURIFICATION; ACID; OIL; NANOPARTICLES; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology